Preceptoria in teaching about men's health from the perspective of the body in light of Merleau-Ponty: an integrative review (Research, Society and Development, 2020)
The aim of this study is to describe the mediations of the preceptor in the field of human health internship and acting as a transforming agent in the exercise of teaching. This is an integrative review of articles from the LILACS, BDENF and MEDLINE databases and the virtual library SciELO, published between 2011 and 2019. For Merleau-Ponty, every possible experience and access to the world occurs through the body. For man, physical strength and sexuality are striking attributes of his body. Theoretical disciplines reaffirm this view, but do not relate it to male specificities and practice issues. The .preceptor nurse brings to his relationship with the undergraduate student the ability to listen, speak and observe, teaching him to care respecting male conceptions. It is concluded that teacher preceptors should lead undergraduates to actions based on this practice.